Effect of alloying on the corrosion behaviour of FeB metallic glasses in sulphuric acid - Singh I.B.; Chaudhary R.S.; Namboodhiri T.K.G. (My University, 2025)
The corrosion behaviour of seven metallic glasses based on the FeB system, namely (i) Fe40Ni40B20 (Vitrovac 0040), (ii) Fe40Ni38Mo4B18 (Metglas 2826MB), (iii) Fe39Ni39Mo2(SiB)20 (Vitrovac 4040), (iv) Fe40Ni40P14B6 (Metglas 2826), (v) Fe32Ni36Cr14P12B6 (Metglas 2826A), (vi) Fe78B13Si9 (Metglas 2605-S-2) and (vii) Fe67Co18B14Si1 (Metglas 2605Co), was investigated in H2SO4 solutions of various concentrations (0.001-0.1 M) using mass loss and electrochemical techniques. In exposures of up to 6 days the corrosion rate in 0.1 M H2SO4 changed in the following order: 2826A < 2826 < 0040 < 2826MB < 4040 < 2605Co < 2605-S-2. During anodic polarization the alloys 2605-S-2, 2605Co and 0040 did not exhibit passivation whereas the remaining four alloys passivated in all the H2SO4 solutions used. Icorr, Icrit and Ipass for these metallic glasses were found to be dependent on the concentration of the corrodent. Icorr and Icrit for all the alloys decreased with decreasing H2SO4 concentration. Ipass for Metglas 2826 and 2826MB increased with decreasing acid concentration while the opposite effect was found for the other two passivating alloys. The present results showed that the corrosion resistance of FB-based metallic glasses depends on the alloying elements present in them. Their corrosion resistance increased by alloying with metals whose effectiveness increased in the following order: cobalt, molybdenum, nickel and chromium. Similarly, metalloids were effective in increasing corrosion resistance in the following order: silicon, boron and phosphorus. The passive film formed on Metglas 2826A alloy was found to be more stable than those on alloys 2826, 2826MB and 4040. © 1986.